STRUCTURAL AND MECHANICAL CHARACTERIZATION OF TUNGSTEN NITRIDE COATINGS PREPARED BY DC SPUTTERING AT CYLINDER LINER - Haerul Ahmadi; Ihwanul Aziz; Dewi Lanita Sari; Idawati Supu (Media Mesin: Majalah Teknik Mesin, 2023)
The cylinder liner is a tube that protects the piston and is a place for the combustion process. The combustion process causes continuous friction to make the cylinder liner wear out. Therefore the cylinder liner must be made of materials that have high hardness. To obtain a high hardness level, surface treatment with DC sputtering techniques is carried out. Surface treatment with DC sputtering technique for 120 minutes with variations of Argon gas and Nitrogen gas 70:30, 80:20, and 90:10. Based on the XRD test results, all treated samples contained a WN layer. The crystal structure of the raw material samples is hexagonal, and the crystal structure of all processed samples is cubic. Vickers hardness characterization shows that the raw material is 110.93 HV. While the sample treated with Ar70:N30 was 234.66 HV. The optimum hardness occurred in samples treated with Ar80:N20 with a hardness of 311.87 HV. However, the Ar90:N10 treatment experienced a decrease in hardness to 130.44 HV. Based on the results of thin film testing, WN affects the increase in the hardness of the cylinder liner material. This is evidenced by the increase in hardness in samples coated with WN.